Report Formatting System (RFS) for FYP Projects - Mohd Nor, Ahmad Khushairy (Universiti Teknologi PETRONAS, 2009)
Conducting aFinal Year Project (FYP) at UTP often needs lecturers to be the supervisors for the students to ensure that the projects run smoothly and follow the requirements and objectives ofthe FYP itself. Even though the projects run on track but there is aproblem faced by the lecturers especially on the format of the reports submitted by the students. When they are doing the FYP, the student have to submit reports such as Preliminary Report, Progress Report, Interim Report and others to their supervisors to show some progress regarding their project. However, sometimes they did not follow the format that the FYP committees and coordinator have stated in the guideline. Hence, the format of the report is not standardized between the lecturers and supervisors even though there is a guideline available. Thus, this project intends to develop a web-based system that can help students to simplify the above activities. The system shall provide facilities to the students to choose the type oftheir report and then the system will show the only format for that report. In order to prepare this system in an effective way, many considerations need to be looked into which requires some research of the suitable programming language or software that will be used for developing this system. Interviews with FYP committees and coordinator have been conducted to clarify the real format of the report which is important to the development of the system. Once the system has been developed, a testing will be conducted that involved FYP students to test it to get the feedback in order to improve the system. The project itself will be developed based on the Phased Development-based Methodology where it is widely used for practical system development and usually produces more stable and reliable systems. It has four main phases which are planning, analysis, design and implementation. This report presents the objectives, problem statements, scope of study as well as the methodology in further detail. Besides that, relevant literatures are also presented to relate the project with some existing ones. Lastly, the results of the project are presented and discussed, and conclusions are drawn from them. IV